2022
DOI: 10.1186/s12877-022-02767-4
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of primary healthcare services among frail older adults – findings from the Helsinki Birth Cohort Study

Abstract: Background The impact of frailty on primary healthcare service use, especially general practice office visits and remote contacts, is currently unknown. Further, little is known about the association of frailty with physiotherapy contacts. Methods We examined the utilization of primary healthcare services among 1064 participants from the Helsinki Birth Cohort Study between the years 2013 and 2017. Frailty was assessed based on Fried’s frailty crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
1
2
0
1
Order By: Relevance
“…According to the obtained results, frailty was related to the use of some health services. Although the studies that explore this association are scarce, 26,27 similar results to those reported in the present investigation were identified. The route whereby this association occurs is complex, with intermediate factors (mainly clinical) that can make the relationship hard to understand.…”
Section: Discussionsupporting
confidence: 88%
“…According to the obtained results, frailty was related to the use of some health services. Although the studies that explore this association are scarce, 26,27 similar results to those reported in the present investigation were identified. The route whereby this association occurs is complex, with intermediate factors (mainly clinical) that can make the relationship hard to understand.…”
Section: Discussionsupporting
confidence: 88%
“…De acuerdo con los resultados obtenidos, la fragilidad se relacionó con el uso de algunos servicios. Si bien son escasos los estudios que exploran esta asociación, 26,27 se identificaron resultados similares a los de la presente investigacion. La vía por la cual se da esta asociación es compleja, con factores intermedios (principalmente clínicos) que pueden dificultar el entendimiento de la relación.…”
Section: Discussionunclassified
“…According to estimations, around 10% of people older than 65 years and about 25–50% of people older than 85 years are frail [ 3 ], and this prevalence is rising [ 4 ]. As frailty and co-morbidity go hand in hand [ 5 ], frail individuals exploit a significant amount of health care resources, thus increasing the economic burden [ 6 ].…”
Section: Introductionmentioning
confidence: 99%